(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This study explores the historical formation and cultural transformation of headdresses and ornaments in the Khorezm oasis. By tracing influences from ancient civilizations, Silk Road exchanges, Soviet-era restrictions, and post-independence revivals, it highlights the dynamic role of adornment in expressing identity, social status, and regional aesthetics. Traditional designs have not only survived but evolved through adaptation and innovation. The research underscores how these accessories serve as living symbols of Khorezm’s rich cultural heritage and its ongoing dialogue with modernity.